Ocular Surface and Tear Film Characteristics in a Sclerodermatous Chronic Graft-Versus-Host Disease Mouse Model. Issue 4 (April 2018) - He, Jingliang; Yamane, Mio; Shibata, Shinsuke; Fukui, Masaki; Shimizu, Eisuke; Yano, Tetsuya; Mukai, Shin; Kawakami, Yutaka; Li, Shaowei; Tsubota, Kazuo; Ogawa, Yoko
Abstract : Purpose: To report the characteristics of the ocular surface in a previously established sclerodermatous chronic graft-versus-host disease (cGVHD) mouse model. Methods: The ocular surface features and tear film parameters of the mouse model were assessed by histopathology, immunohistochemistry, electron microscopy, quantitative polymerase chain reaction, and flow cytometry. Results: The mice exhibited loss of body weight and decreased tear secretion ( P < 0.001), mimicking the clinical features of patients with cGVHD. Ocular examination demonstrated significant corneal epithelial staining, conjunctival ( P < 0.001), and eyelid ( P = 0.015) fibrosis compared with the control mice. The density of both goblet cells ( P = 0.043) and microvilli was lower ( P < 0.001), and the microvilli were shorter ( P = 0.007) in the conjunctiva of cGVHD mice than those of the controls. The immunohistochemical studies demonstrated greater expression of CD45 +, CD4 +, and CD8 + cells in the conjunctiva and eyelid tissues compared with the controls ( P < 0.05 for all). In addition, reduced Forkhead box P3 (Foxp3)+ cells were found in both the peripheral blood ( P < 0.001) and conjunctiva ( P = 0.042) of cGVHD mice compared with the controls. Conclusions: The constellation of these findings suggests that the sclerodermatous cGVHD mouse model well recapitulates ocular manifestations of cGVHD in humans. This model can be used to study the mechanisms involved in the pathogenesis and treatment of chronic ocular graft-versus-host disease. Abstract : Supplemental Digital Content is Available in the Text.